2011
DOI: 10.1007/s10495-011-0587-z
|View full text |Cite
|
Sign up to set email alerts
|

Apoptotic regulation of epithelial cellular extrusion

Abstract: Cellular extrusion is a mechanism that removes dying cells from epithelial tissues to prevent compromising their barrier function. Extrusion occurs in all observed epithelia in vivo and can be modeled in vitro by inducing apoptosis in cultured epithelial monolayers. We established that actin and myosin form a ring that contracts in the surrounding cells that drives cellular extrusion. It is not clear, however, if all apoptotic pathways lead to extrusion and how apoptosis and extrusion are molecularly linked. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
68
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(74 citation statements)
references
References 50 publications
4
68
2
Order By: Relevance
“…These results contrast with the extrusion observed in crowding-induced delamination in the Drosophila melanogaster notum, where rosette formation around the delaminating cell is driven by increased myosin contractility in the surrounding cells (Marinari et al, 2012). The present data suggest an 'altruistic' role for the dying cell during cell extrusion (Andrade and Rosenblatt, 2011;Mills et al, 1999). Cortical F-actin enrichment in the dying cell has been observed previously in MDCK monolayers, but the authors concluded that it did not participate in extrusion based on the lack of effect of C3-toxin (an inhibitor of RhoA, RhoC and cdc42) injected into the dying cell (Rosenblatt et al, 2001).…”
Section: Discussioncontrasting
confidence: 71%
See 1 more Smart Citation
“…These results contrast with the extrusion observed in crowding-induced delamination in the Drosophila melanogaster notum, where rosette formation around the delaminating cell is driven by increased myosin contractility in the surrounding cells (Marinari et al, 2012). The present data suggest an 'altruistic' role for the dying cell during cell extrusion (Andrade and Rosenblatt, 2011;Mills et al, 1999). Cortical F-actin enrichment in the dying cell has been observed previously in MDCK monolayers, but the authors concluded that it did not participate in extrusion based on the lack of effect of C3-toxin (an inhibitor of RhoA, RhoC and cdc42) injected into the dying cell (Rosenblatt et al, 2001).…”
Section: Discussioncontrasting
confidence: 71%
“…The multicellular ring descends basally and, once it reaches the base of the monolayer, lamellipodial protrusions originating from the neighbouring cells join below the dying cell, reforming intercellular junctions that extrude the dead cell (Tamada et al, 2007). Based on these studies, the current consensus is that the dying cell provides a biochemical signal for its neighbours but plays no mechanical role in its own extrusion (Andrade and Rosenblatt, 2011;Cai and Sheetz, 2009;Gu and Rosenblatt, 2012). However, detailed time-resolved observations of actomyosin dynamics during cell extrusion are lacking, making a thorough understanding of the biological and biophysical mechanisms of extrusion impossible.…”
Section: Introductionmentioning
confidence: 99%
“…Apical cell extrusion in a wild-type epithelial monolayer is normally coupled to apoptosis (Andrade and Rosenblatt, 2011;Kuipers et al, 2014;Lubkov and Bar-Sagi, 2014). Accordingly, we observe that 31.661.8% (6s.e.m.)…”
Section: Cell Extrusion Driven By E-cad Cleavage Precedes Apoptosismentioning
confidence: 62%
“…Blotting was performed using antibodies against HA, E-cadEC, E-cadCD and a-tubulin. the induction of apoptosis (Rosenblatt et al, 2001;Andrade and Rosenblatt, 2011).…”
Section: Cell Extrusion Driven By E-cad Cleavage Precedes Apoptosismentioning
confidence: 99%
See 1 more Smart Citation